Intra-Ligamentous Pigmented Villonodular Synovitis of the Anterior Cruciate Ligament, a Case Report - Hesham Mohamed Gawish; Mohamed Abdel Monsef Elghaish; Emam Mohamed Ahmed; Mohamed Abdalla Mahfouz; Waleed Hamed Aziz; Ahmed Hassan Waly (Journal of Orthopaedic Case Reports)
Introduction: Pigmented villonodular synovitis arising from cruciate ligaments is a very rare condition. Arthroscopic management of these lesions is the treatment of choice. Probing of the anterior cruciate ligament (ACL) is very crucial due to the possibility of intraligamentous invasion of this lesion. Case Report: A 40-year-old male patient had anterior knee pain and effusion without giving way. There was no history of trauma before the presentation. In his last attack of locking, he had knee effusion for the 1st time. His magnetic resonance imaging scan revealed partial ACL injury along with intercondylar notch soft-tissue mass, i.e., nodular synovitis. The lesion was seen between the ACL and lateral femoral condyle during arthroscopy. The rest of the lesion was inside the substance of the ACL. After the complete removal of the lesion, ACL reconstruction was done. Microscopic examination revealed a localized pigmented villonodular synovitis. Conclusion: Specific signs and symptoms for pigmented villonodular synovitis are lacking. Surgeons should have a very high suspicion of intra-articular localization for this type of lesion. Preparation of ligamentous reconstruction is recommended in case of complete ligamentous invasion by the tumor.